Colour hunting : how colour influences what we buy, make and feel - Tan, Jeanne; Kamphuis, Hanneke; Van Onna, Hedwig (Amsterdam : Frame, 2011)
For millennia, artists and designers have utilized colour to express ideas and emotions in everything from the frescoes and textiles of ancient civilizations to the haute couture and digitally created architecture of today. Colour plays a vital role in our visual experiences and affects senses such as feeling and taste, but it also shapes our actions subconsciously. This book explores the very depths of the subject--Publisher's website.
boek